Spz/Toll-6 signal guides organotropic metastasis in Drosophila - Ketu Mishra-Gorur; Daming Li; Xianjue Ma; Yanki Yarman; Lei Xue; Tian Xu (The Company of Biologists, 2019)
Targeted cell migration plays important roles in developmental biology and disease processes, including in metastasis. Drosophila tumors exhibit traits characteristic of human cancers, providing a powerful model to study developmental and cancer biology. We now find that cells derived from Drosophila eye-disc tumors also display organ-specific metastasis, invading receptive organs but not wing disc. Toll receptors are known to affect innate immunity and the tumor inflammatory microenvironment by modulating the NF-κB pathway. Our RNA interference (RNAi) screen and genetic analyses show that Toll-6 is required for migration and invasion of the tumor cells. Further, receptive organs express Toll ligands [Spätzle (Spz) family molecules], and ectopic Spz expression renders the wing disc receptive to metastasis. Finally, Toll-6 promotes metastasis by activating JNK signaling, a key regulator of cell migration. Hence, we report Toll-6 and Spz as a new pair of guidance molecules mediating organ-specific metastatic behavior and highlight a novel signaling mechanism for Toll-family receptors.